Pengaruh Pelayanan Panitia Penerimaan Taruna Terhadap Kepuasan Calon Taruna Serta Dampaknya Terhadap Loyalitas Taruna di Poltekpel Banten - Rikardo, Dapid; Nursyamsu, Nursyamsu; Herningsih, Siwi Woro; Adil, Muhammad Kemal (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2024)
The alteration of Training Center to Higher Education can be a driving factor in improving the service quality in Poltekpel Banten considering Poltekpel Banten is a new college competing with other existing nautical polytechnics. Especially with the support of Human Resources Development Agency in giving additional quota for student admission each year. The credibility of Poltekpel Banten is reflected through the service quality, customer satisfaction and customer loyalty. This study is conducted in Poltekpel Banten from January to June 2022 using quantitative approach with survey method. The data is analyzed with SEM AMOS and processed in deductive manner. The variables studied are service quality, customer satisfaction, and customer loyalty. The sample in this study 224 student candidates from all the student candidates of Poltekpel Banten during July to December 2022. The data is collected using questionnaire. From the four hypotheses tested in this study, two of them are giving significant results and the other two is not significant.